Cisco CCNP ENARSI v1.1 (300-410) Cert Prep: 3 Infrastructure Security. - Wallace, Kevin (linkedin.com, 2020)
Study for the third domain of the Cisco ENARSI certification exam: Infrastructure Security. Learn about troubleshooting secure VPN, IPv4, and IPv6 technologies.